La normalización documental en las revistas científicas españolas sobre discapacidad. - Porras, M.P.; Verdugo, M.Á. (Revista General de Información y Documentación, 2004)
This work evaluates the Spanish scientific journals dealing with disability. The panorama in this field is very heterogeneous owing to the great quantity of journals in some subject areas and the lack in others, the customary limited editions and the scant aid given to journals. Information about the quality and the presentation of the articles in scientific journals and the publication itself is given. To this end, a questionnaire based on UNE standards was devised to analyse the points previously mentioned. The results obtained demonstrate the good level of standardization of Spanish scientific journals.
Keywords: Disability; Standardization; Scientific journals